Influence of public hospital reform on public health: Evidence from a quasi-natural experiment in China - Guo, Bingnan; Feng, Weizhe; Cai, Huilin; Lin, Ji (Frontiers in Public Health, 2023)
Public health is an important symbol of national wealth and prosperity. At present, China's public health is hindered by the poor management of public hospitals, which impacts the demographic structure and socioeconomic development. Therefore, taking the implementation of public hospital reform in China as a quasi-natural experiment, this study employed the time-varying DID model and the mediating effect to evaluate the influence of public hospital reform on public health. The results were as follows: (1) Public hospital reform can significantly improve public health, and a series of robustness tests have also confirmed the effects; (2) Government's financial support is a transmission mechanism for public hospital reform to promote public health; (3) After taking control variables into consideration, the effect of public hospital reform is stronger in the western region with a poorer economy. This research provides a vital policy reference for promoting the scope of reform and improving the health of the general public.